Dependence of the Ice Formation Activity of Dioxynaphthalenes, Fluoroglucin and Silver Iodide on the Structure of the Hydrate Shells of Their Crystals - V.V. Turov; A.V. Turov; A.V. Arkharov (Adsorption Science & Technology)
The 1 H NMR spectroscopy of frozen suspensions has been used to investigate the hydrate shells of Agl, fluoroglucin (FG) and dioxynaphthalenes (DON). It has been shown that the ice formation activity (IFA) of the above compounds may be correlated with the inverse thickness of their associated adsorbed water layer and with the free energy of the strongly bound water film. All the compounds studied formed an ice layer at the substance/ice interface in which the mobility of the water molecules has a value which is intermediate between that for water molecules in ice and for adsorbed water molecules. The ratio between the thickness of the layer of ‘mobile’ ice and that of the layer of adsorbed water increased as a function of IFA.